The rational design of highly stable, amphiphilic helical peptides - Chmielewski, J; Lipton, M (International journal of peptide and protein research, 1994)
A computer algorithm was devised for the evaluation of helical stability of potentially amphiphilic peptide sequences of specified length containing a set number of leucines in the hydrophobic region. All possible combinations of Glu, Lys and Gln in the hydrophilic region are rated using a set of empirical rules for salt bridge formation in alpha-helices, and the sequences which rate the highest are displayed. The rules for salt bridge formation were largely derived from published studies on the effects of salt bridges on helical stability. The algorithm was tested by redesigning a known amphiphilic alpha-helical peptide, alpha 1B or 1, which has been shown to aggregate into four-helix bundles. Comparison of the circular dichroism spectra of two peptides, 2 and 3, to 1 demonstrated that the redesigned peptide with the highest priority score from the algorithm, 2, was more helical when aggregated and slightly more helical as a monomer, whereas the peptide with the low priority score, 3, was somewhat less helical when aggregated and much less helical when monomeric. These results support the design of the algorithm, although conclusions based on aggregation data are complicated by the importance of interhelix contacts in the bundle. Further studies are underway to examine the reliability of the algorithm's predictions regarding the design of other helical peptides.